Hormonal Contraception at Menopause Age in Neighborhood V Baru Ladang Bambu Village, Medan Tuntungan District, 2019 - Sari Rahma Fitri; Nurdiana Manurung (Science Midwifery, 2020)
The purpose of this research is to increase the knowledge and insight of young women about what often occurs in adolescents related to the early period of reproductive organ maturity in adolescents is the problem of pregnancy that occurs outside of marriage. And the limited knowledge of young women about sexual health can increase the risk of pregnancy. Increase the knowledge of students/adolescent girls about sexually transmitted infections. Increase knowledge and explain to young women about the limited knowledge of adolescents about sexual health that can increase the risk of pregnancy. The type and form of activity of this activity is the provision of material to female students/teenagers about reproductive health and sexually transmitted diseases. Explain the impact of sexually transmitted infections to young women. To achieve the objectives of the above activities, activities were carried out including providing counseling to young women about sexually transmitted infections in the Ladang Bambu Village, Medan Tuntungan District.